2022
DOI: 10.1037/edu0000614
|View full text |Cite
|
Sign up to set email alerts
|

Promoting an agentic orientation: An intervention in university psychology and physical science courses.

Abstract: Agentic engagement, or attempts to proactively influence instruction, predicts positive classroom climate and students' motivation. As such, it is a potentially effective target for intervention, though causal evidence is limited. This investigation explored whether an agentic orientation could be cultivated through a brief, online intervention for university students and the potential benefits of such an intervention. Three randomized field experiments with college students in psychology (Study 1 and Study 2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 81 publications
1
17
0
Order By: Relevance
“…Similarly, students who perceived higher autonomy-supportive teaching at one point in the flow of instruction subsequently reported greater agentic engagement at a later point in the flow of instruction, compared to other students who perceived a lower level of autonomy-supportive teaching. This result replicated and confirmed existing findings from twowave longitudinal studies, experimental studies, and an overall group of studies testing the unidirectionality of the teacherfacilitating path or the student-facilitating path (Bordbar, 2019(Bordbar, , 2021Jiang & Zhang, 2021;Matos et al, 2018;Michou et al, 2023;Patall et al, 2019Patall et al, , 2021Reeve, 2013;Reeve et al, , 2022. This reciprocal interplay was invariant over the four time waves.…”
Section: Reciprocal Relation In Between-and Within-person Perspectivessupporting
confidence: 85%
See 1 more Smart Citation
“…Similarly, students who perceived higher autonomy-supportive teaching at one point in the flow of instruction subsequently reported greater agentic engagement at a later point in the flow of instruction, compared to other students who perceived a lower level of autonomy-supportive teaching. This result replicated and confirmed existing findings from twowave longitudinal studies, experimental studies, and an overall group of studies testing the unidirectionality of the teacherfacilitating path or the student-facilitating path (Bordbar, 2019(Bordbar, , 2021Jiang & Zhang, 2021;Matos et al, 2018;Michou et al, 2023;Patall et al, 2019Patall et al, , 2021Reeve, 2013;Reeve et al, , 2022. This reciprocal interplay was invariant over the four time waves.…”
Section: Reciprocal Relation In Between-and Within-person Perspectivessupporting
confidence: 85%
“…Through their acts of agentic engagement, students help teachers become aware of what students want, need, and are interested in doing, and this awareness may change how the teacher interacts with students during instruction. Accordingly, such student agency tends to longitudinally increase the teacher’s autonomy-supportive instructional behavior (Matos et al, 2018; Patall et al, 2021; Reeve et al, 2020). Students’ agentic engagement is educationally important not only because such acts of agency help students create a more supportive learning environment for themselves but also because they enable greater academic motivation, learning, and achievement (Patall et al, 2021; Reeve, 2013; Reeve et al, 2020, 2022; Reeve & Tseng, 2011).…”
Section: Teacher-facilitating and Student-facilitating Pathsmentioning
confidence: 99%
“…Beyond these teacher and student factors, the literature suggests that students who agentically engage may do so because of an underlying belief that such behavior will actually change their learning experiences. In a randomized controlled trial, Patall and colleagues (2021) randomly assigned undergraduate college students in chemistry and physics courses to a web-based agentic engagement orientation intervention or one of two control conditions. They found that students who received the target (agentic) intervention reported a more agentic mindset (an orientation toward viewing their motivation and instructor practice as malleable and responsive to agentic behaviors), which in turn, predicted greater student-reported in-class engagement, instructor autonomy support, and need satisfaction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Specifically, depending on the direction, i.e., positive or negative, and valence, i.e., activating or deactivating, cognitive engagement will vary (Pekrun and Linnenbrink-Garcia, 2012;Pekrun and Marsh, 2022). For example, it is reasonable to predict that students who show more excitement and greater levels of activity during a task (positive activating emotions), along with more agency, will also have greater levels of cognitive engagement, e.g., greater skill use, and sense of control over their engagement and learning (Patall et al, 2022). Alternatively, it is reasonable to predict that students who show greater levels of stress and anxiety during a task (negative activating emotions) will have lower levels of cognitive engagement because they will be attending to their stress and anxiety.…”
Section: Momentary Emotions As a Mediatormentioning
confidence: 99%
“…Based on our prior research (Torsney et al, 2022) and the theoretical underpinning of John Henryism as a precursor for engagement, we hypothesize that John Henryism will activate the CVT and momentary engagement system. That is, John Henryism will mediate relationships among specific demographics by increasing control (Brody et al, 2020;Patall et al, 2022) and value, increasing positive emotions and lowering negative emotions (Gaydosh et al, 2018;Robinson and Thomas Tobin, 2021), and increasing cognitive engagement (Torsney et al, 2022).…”
Section: Current Studymentioning
confidence: 99%